2015
DOI: 10.1177/0954411915604336
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial stress relaxation of semilunar heart valve leaflets during simulated collagen catabolism: Effects of collagenase concentration and equibiaxial strain state

Abstract: Heart valve leaflet collagen turnover and remodeling are innate to physiological homeostasis; valvular interstitial cells routinely catabolize damaged collagen and affect repair. Moreover, evidence indicates that leaflets can adapt to altered physiological (e.g. pregnancy) and pathological (e.g. hypertension) mechanical load states, tuning collagen structure and composition to changes in pressure and flow. However, while valvular interstitial cell-secreted matrix metalloproteinases are considered the primary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Furthermore, the group of Bodi showed that in swine, and more importantly in human, the collagen organization at the outer region of the myocardial infarcted area was more disorganized and random compared to the core region [11]. Other mechanical properties that changed during valvular ECM remodeling have been shown to affect VIC phenotypic change and functions, for example stress relaxation [12] and transvalvular pressure [13]. For this manuscript, we are specifically interested in the effect of randomized stiffness organization, which results from new deposited collagen fibers on VIC phenotypic change.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the group of Bodi showed that in swine, and more importantly in human, the collagen organization at the outer region of the myocardial infarcted area was more disorganized and random compared to the core region [11]. Other mechanical properties that changed during valvular ECM remodeling have been shown to affect VIC phenotypic change and functions, for example stress relaxation [12] and transvalvular pressure [13]. For this manuscript, we are specifically interested in the effect of randomized stiffness organization, which results from new deposited collagen fibers on VIC phenotypic change.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of collagen are thought to be protected from enzymatic breakdown under low and moderate forces, but are made vulnerable to degradation by higher forces, as large deformations expose sites of protease binding [25][26][27]. In a collagen network under high pre-stretch (e.g.…”
Section: Delayed Restoration Of Homeostasismentioning
confidence: 99%
“…It is worth noting that cells are not the only components that are sensitive to changes in mechanical loading [ 43 ]. While large mechanical strains could increase the rate of extracellular matrix catabolism in cardiac valves [ 44 ], studies have shown that the extracellular matrix collagen is more stable and degrades more slowly under homeostatic mechanical strain [ 45 47 ]. Considering such an important influence of the tissue mechanical milieu on short-term as well as long-term valve responses, it is essential to not ignore dilation in the annulus following chordae rupture.…”
Section: Discussionmentioning
confidence: 99%